SSDHT:social network-based secure DHT mechanism - Panpan LI; Zhengxia XIE; Guangxue YUE; Bolin MA; Li CHEN; Jianhua LIU (Dianxin kexue)
P2P systems have been widely used in the field of file sharing,etc.However,DHT (distributed hash table) networks have no center,no authentication,and lack of node authentication mechanism,making existing DHT-based P2P systems vulnerable to external attacks such as Sybil attacks.A DHT security enhancement mechanism based on social network was proposed,which introduced the trust relationship of nodes in the social network into the DHT network to improve the recognition ability of Sybil nodes.The KAD (Kademlia) algorithm was used as an example to verify the experiment.Experimental results based on Facebook and Twitter datasets show that the proposed security mechanism is suitable for large-scale dynamic networks and can effectively defend against Sybil attacks.